SAT-LB44 WNT2B Regulates Adrenocortical Progenitor Cell Fate And Zona Glomerulosa Identity In Vivo - Little, Donald W (J Endocr Soc, 2020)
Dysregulation of normal adrenal structure and function contributes to a spectrum of diseases from hypoplasia to cancer. Peripheral adrenocortical progenitor cells in the zona glomerulosa (zG) centripetally migrate and differentiate to replenish steroidogenic cells of the zG and the inner cortex over time (1). Both the fate of progenitor cells and aldosterone production by steroidogenic cells in the zG are regulated by Wnt signaling (2,3), but the cell-specific effects of individual Wnt ligands in the adrenal are not fully understood. To further characterize Wnt signaling components crucial for progenitor cell maintenance and zG identity, we analyzed mouse adrenals using single molecule in situ hybridization (smISH), which revealed the previously unknown expression of Wnt2b exclusively in the adrenal capsule. Wnt2b is co-expressed with the Wnt signaling potentiator Rspo3, the loss of which causes zG depletion and reduced adrenal size in mice (4). Therefore, we hypothesized that capsular WNT2B activates Wnt signaling in the underlying cortex to maintain the undifferentiated state of progenitor cells. To define the role of WNT2B in these processes, we generated Wnt2b conditional knockout (cKO) mice by crossing a capsule-specific Gli1-CreERT2 driver (5) and a floxed Wnt2b allele (6). We administered tamoxifen to 6-week-old male mice and assessed the effects of Wnt2b loss 4 weeks later. Gli1-CreERT2 activation significantly decreased Wnt2b expression (P<0.001) and resulted in a lower adrenal to body weight ratio in Wnt2b cKOs compared to controls (P<0.05). Adrenocortical proliferation (Ki67) was significantly decreased in Wnt2b cKO mice (P<0.0001), suggesting that WNT2B may mediate progenitor cell self-renewal. To characterize the effect of WNT2B loss on Wnt signaling, we assessed activation of the primary Wnt effector β-catenin. High β-catenin activity in the zG observed in wild-type mice was disrupted in Wnt2b cKO mice, together with markedly reduced expression of adrenocortical Wnt target genes Axin2 and Wnt4. In addition, Wnt2b loss resulted in downregulation of steroidogenic genes Cyp11b2 (P=0.0139) and Hsd3b6 (P=0.0679). Together, these data suggest that capsule-derived WNT2B activates cortical Wnt signaling to maintain the identity of both undifferentiated progenitor cells and differentiated steroidogenic cells of the zG, which has important implications for adrenal homeostasis and disease, including both primary adrenal failure and neoplasia. References: (1) King et al., PNAS, 2009 Dec 15;106(50):21185-90. (2) Berthon et al., Hum Mol Genet., 2010 Apr 15;19(8):1561-76. (3) Heikkila et al., Endocrinol., 2002 Nov;143(11):4358-65. (4) Vidal et al., Genes & Dev., 2016 Jun 15;30(12):1389-94. (5) Ahn & Joyner, Cell, 2004 Aug 20;118(4):505-16. (6) Tsukiyama & Yamaguchi, Neurosci Lett., 2012 Mar 14;512(1):48-52.